ОБ’ЄКТИ ТА СУБ’ЄКТИ КОРПОРАТИВНИХ ВІДНОСИН: НАПРЯМИ ДОСЛІДЖЕНЬ - Volovyk, O.A. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The content of corporative relations according to the legal and doctrine definitions has been researched. The category of corporative rights has been considered; grounds for their content differences have been determined. Specific objects and subjects of corporative relations have been analyzed, prospects for legal development in the given sphere have been identified.